Phyto-fabricated Nanoparticles and Their Anti-biofilm Activity: Progress and Current Status - Das, Puja; Ghosh, Sayantan; Nayak, Bismita (Frontiers in Nanotechnology, 2021)
Biofilm is the self-synthesized, mucus-like extracellular polymeric matrix that acts as a key virulence factor in various pathogenic microorganisms, thereby posing a serious threat to human health. It has been estimated that around 80% of hospital-acquired infections are associated with biofilms which are found to be present on both biotic and abiotic surfaces. Antibiotics, the current mainstream treatment strategy for biofilms are often found to be futile in the eradication of these complex structures, and to date, there is no effective therapeutic strategy established against biofilm infections. In this regard, nanotechnology can provide a potential platform for the alleviation of this problem owing to its unique size-dependent properties. Accordingly, various novel strategies are being developed for the synthesis of different types of nanoparticles. Bio-nanotechnology is a division of nanotechnology which is gaining significant attention due to its ability to synthesize nanoparticles of various compositions and sizes using biotic sources. It utilizes the rich biodiversity of various biological components which are biocompatible for the synthesis of nanoparticles. Additionally, the biogenic nanoparticles are eco-friendly, cost-effective, and relatively less toxic when compared to chemically or physically synthesized alternatives. Biogenic synthesis of nanoparticles is a bottom-top methodology in which the nanoparticles are formed due to the presence of biological components (plant extract and microbial enzymes) which act as stabilizing and reducing agents. These biosynthesized nanoparticles exhibit anti-biofilm activity via various mechanisms such as ROS production, inhibiting quorum sensing, inhibiting EPS production, etc. This review will provide an insight into the application of various biogenic sources for nanoparticle synthesis. Furthermore, we have highlighted the potential of phytosynthesized nanoparticles as a promising antibiofilm agent as well as elucidated their antibacterial and antibiofilm mechanism.